Effect of Formal Course of Information Literacy on Student Performance / Sajjad Ur Rehman and Suha Al-Awadhi - Ur Rehman, Sajjad; Al-Awadhi, Suha (2011)
This course has been in place for the last two years. This study was designed to assess the relevance, usefulness and effect of this course on developing the needed capabilities among students. The study had two purposes; first, studying if the course had made any significant difference in the information literacy and research capabilities of students. Secondly, it assessed whether certain personal and social variables of students were associated with significance differences in student capabilities. A research instrument was designed around the constructs that had been defined in the course description and syllabi of 1380-131. This instrument was administered in the first week of the Semester 1 classes of the year 2009-10 in five sections of the same class. The same instrument, with changed facts and multiple choice statements, was administered in the last week of the same semester in the same five sections. Students also provided information about personal and social variables. Data were analyzed and it was found that the students performed significantly better for the overall information literacy and for the three segments of information, computing and research. Majors of students, types of schools they had attended and mother‘s academic qualifications were found to be associated with significant differences in students‘ performance on information literacy measures.